Mapping as Harm Reduction: Using GIS to Map Chatter Associated with Sex Work - Towers, Ashley E. (Victims & offenders, 2022)
Although geographic information systems (GIS) are popular tools for investigations and resource deployment/management within law enforcement agencies, the utility of software programs like Esri’s ArcGIS mapping software to identify vulnerable areas or populations to prevent or mitigate the impact of crime is rarely explored within the field. What is even less explored is how online information can be leveraged and mapped to inform practitioners of areas where harm reduction strategies could be deployed. Recognizing this gap in the literature, this investigation explored whether publicly available online chatter by established and potential customers of sex workers could point to areas of targeted outreach before harm occurs. Ultimately, we found that online chatter about accessing sex workers can be mapped to identify vulnerable areas and people. While this study was exploratory and others should build on this idea, this study demonstrated GIS could aid in the prevention of crime by leveraging online information to highlight areas and people at risk for harm.